Using RegulonDB, the Escherichia coli K‐12 Gene Regulatory Transcriptional Network Database. Issue 1 (9th April 2018) - Salgado, Heladia; Martínez‐Flores, Irma; Bustamante, Víctor H.; Alquicira‐Hernández, Kevin; García‐Sotelo, Jair S.; García‐Alonso, Delfino; Collado‐Vides, Julio
Abstract: In RegulonDB, for over 25 years, we have been gathering knowledge by manual curation from original scientific literature on the regulation of transcription initiation and genome organization in transcription units of the Escherichia coli K‐12 genome. This unit describes six basic protocols that can serve as a guiding introduction to the main content of the current version (v9.4) of this electronic resource. These protocols include general navigation as well as searching for specific objects such as genes, gene products, transcription units, promoters, transcription factors, coexpression, and genetic sensory response units or GENSOR Units. In these protocols, the user will find an initial introduction to the concepts pertinent to the protocol, the content obtained when performing the given navigation, and the necessary resources for carrying out the protocol. This easy‐to‐follow presentation should help anyone interested in quickly seeing all that is currently offered in RegulonDB, including position weight matrices of transcription factors, coexpression values based on published microarrays, and the GENSOR Units unique to RegulonDB that offer regulatory mechanisms in the context of their signals and metabolic consequences. © 2018 by John Wiley & Sons, Inc.